Turbo Coding for 4G Systems: Design Issues and Solutions 10.14209/jcis.2003.5 - Giulietti, Alexandre; Strum, Marius; Bougard, Bruno; van der Perre, Liesbet (Journal of Communication and Information Systems, 2015)
After the initial interest caused by the appearance of turbo codes in 1993, special attention on the implementation has led to their adoption in some of the most important 3G standards. However, future broadband systems (with data rates up to 155 Mb/s) still require a better speed/latency/power performance than those found in current implementations. This paper discusses several design aspects of a broadband, low-power turbo codec owning features that enable its application in the incoming decade systems. The presented ideas were applied to an 80 Mb/s, 2 nJ/bit turbo codec core with latency smaller than 10ms. This flexible architecture allows re-scaling towards faster low power implementations (beyond 1 Gb/s).